Job Satisfaction of Commercial Bank Employees in Bangladesh: An Empirical Study - Kumar, Dhanonjoy (ABC Journal of Advanced Research, 2016)
The progress of any organization is absolutely dependent on the skillful utilization of its human resources. It is not a machine but man – thoroughly motivated and completely dedicated that helps a firm’s profit curve soaring upward. Human resources are the only strategic resources that can make a notable difference between two or more firms in respect of their goal-attainment. Job satisfaction of employees has been recognized now-a-days as a pre-requisite for achieving the organization’s goals.  In fact, it makes a significant contribution towards enhancing the firm’s overall performance. It is well accepted that the higher the level of job satisfaction of employees, the greater is the contribution of employees to the organization. The present paper seeks to analyze job satisfaction of bank employees in Bangladesh. It focuses on the relative importance of job satisfaction factors and their impact on the overall job satisfaction of employees. In this study the Minnesota Satisfaction Questionnaire (MSQ- Long Form) was used in measuring satisfaction levels of 20 job facets and general job satisfaction. While tackling the issue addressed in the study relevant statistical tools and techniques were applied at appropriate places. The study revealed that the majority of the respondents were found satisfied with their jobs. It also observes that all job-related variables had a positive influence on the job satisfaction.